HUBUNGAN KONSUMSI MAKANAN CEPAT SAJI DENGAN DISMENOREA PRIMER PADA REMAJA PUTRI DI SEKOLAH MENENGAH KEJURUAN - Ayu, Larasia Gloria; Yati, Dwi; Suparjo, Suparjo (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
The accumulation of prostaglandins during menstruation results in uterine hypercontraction and pain. The prevalence of primary dysmenorrhea in Indonesia is around 54.89%. The impact of primary dysmenorrhea if not treated immediately is the disruption of learning activities. Fast food plays a role as a risk factor for primary dysmenorrhea. The purpose of this study was to determine the relationship between fast food consumption and primary dysmenorrhea in adolescent girls at SMK. This type of research is quantitative with a cross sectional approach. The population in this study were 63 adolescent girls of SMK Koperasi Yogyakarta. The sample was determined by stratified random sampling technique with a total of 54 adolescent girls. Data collection was carried out in June 2024. The instruments used were FFQ questionnaire and dysmenorrhea questionnaire. Data analysis was performed using Spearman Rank statistical test. The results showed that the majority of fast food consumption was in the frequent category, namely 29 respondents (53.7%), the majority of dysmenorrhea was in the severe category, namely 28 respondents (51.9%). Statistical test results obtained p-value 0.001 (<0.05) with a very strong relationship (0.833). The direction of the correlation is positive, meaning that the more frequent the consumption of fast food, the more severe the dysmenorrhea experienced. There is a relationship between fast food and primary dysmenorrhea in adolescent girls. It is recommended that adolescent girls avoid consuming fast food and switch to healthy foods so as to reduce primary dysmenorrhea during menstruation